Na2SiO3‐Catalyzed Glycerolysis of Sacha Inchi (Plukenetia volubilis L.) Oil into Di‐ and Monoacylglycerols. (14th April 2020) - Luo, Jia; Wang, Zeping; Deng, Shangzhi; Zhang, Fan; Bao, Guirong; Mao, Junni; Yang, Wenjing
Abstract: Direct glycerolysis of novel edible Sacha Inchi ( Plukenetia volubilis L.) seed oil (PvLO) into diacylglycerols (DAG) and monoacylglycerols (MAG) was studied over solid Na2 SiO3 with or without microwave assistance. The glycerolysis yield was calculated by qualitative and semiquantitative analyses of 1 H NMR, 13 C NMR, and FT‐IR spectra. The yields of ~33% 1, 3‐DAG, ~16% 1, 2‐DAG, ~40% 1‐MAG, and ~2.3% 2‐MAG were achieved after 16 hours at 120 °C in three consecutive cycles using acetone, with an interesterification rate of 92%. The modified oil showed enhanced gelation ability at low temperatures. The yield of 1, 2‐DAG can be increased by adding acetone as solvent. The fatty acid compositions and unsaturated structure of lipids were less destroyed after alkaline glycerolysis. However, more α‐linolenic and linoleic acids were transferred to the sn ‐2 position of glyceryl skeleton. The oxidative stability of the modified oil was still controllable. In summary, this work provides a feasible method to convert polyunsaturated plant oils into oils rich in DAG and MAG with less destructive impact on the olefinic structure of oil. Also, it provides a useful example of how to quickly evaluate the influence of chemical modification on the chemical structure of plant oils by using various spectral technologies.